Chapter El viento de la luna di Antonio Muñoz Molina: spazio terrestre e spazio lunare a confronto - FIORDALISO, Giovanna (Studi e saggi, 2021)
Published in 2006, El viento de la luna is one of Muñoz Molina's latest novels. Set in Mágina, a little town in the Andalusian province, in 1969, it's the story of a boy of thirteen year old fascinated by the events of Apollo XI and its landing on the moon. His observation of the earth and the moon expresses an image of the reality made by a strange mixture of the present and the past, during the last years of Franco's dictatorship. The inverted point of view proposed along the novel through the eyes of the boy opens a new and courageous way of seeing and perceiving events: with such a perspective, the moon looks at the earth and allows the consciousness of a new meaning and a new dimension about life.